The Effect of Red Dragon Fruit Juice Towards Cholesterol Level and Maximum Aerobic Capacity (VO2max) on Sport Science Students Treated with Heavy Physical Exercise. (February 2020) - Harahap, N S; Sunarno, A; Simatupang, N; Suprayitno,
Abstract: Heavy physical exercise causes increased production of free radicals. The accumulation of oxidative stress can reduce cardiorespiratory endurance. VO2 max plays a role as an indicator of the circumstances of cardiorespiratory. An increase in cholesterol levels is a risk factor for coronary heart disease. As a result, there is a decrease in fitness marked by a decrease in the value of VO2 max. The purpose of this study was to determine whether the antioxidant supplement given during heavy physical exercise had a beneficial effect on decrease cholesterol and the increase of VO2 max levels. The subjects were 30 students, male sex, 20-22 years old, divided into 3 groups randomly, each 10 people, group 1: subjects not given heavy physical exercise and only given a placebo (control); group 2: subjects given heavy physical exercise and placebo (HPE-RDF); group 3: subjects given heavy physical exercise and red dragon fruit juice (HPE+RDF). Measurement of cholesterol and VO2 max levels in the pre-test and post-test. The results showed that there was an increase in VO2 max and a decrease in cholesterol (p<0.05) in the HPE + RDF group compared to the HPE-RDF group. The Heavy exercise group given red dragon fruit juice can increase VO2 max and reduce cholesterol levels.